A Low Cost Course Information Syndication System - Ajayi, Anuoluwapo Olanrewaju; Olajubu, Emmanuel; Bello, Sururah Apinke; Soriyan, H.Abimbola (Journal of information technology education, 2023)
volume 10, llp106-llp118